2010
DOI: 10.1002/cncr.25753
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant ABCG2 overexpression and FLT3‐ITD mutation identify a subset of acute myeloid leukemia patients at high risk of relapse

Abstract: BACKGROUND: ABCG2 protein overexpression and FLT3 internal tandem duplication (ITD) correlate with higher relapse rate and shorter disease-free survival (DFS) in acute myeloid leukemia (AML), but no data are available on the possible effect of concomitant presence of these 2 factors. METHODS: The authors analyzed the outcome of 166 cases of adult AML patients who were homogeneously treated with a fludarabine-based induction therapy. RESULTS: ABCG2 overexpression and FLT3-ITD were detected in 83 (50%) and 47 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Co-ordinate regulation of ABCG2 with ABCB1 (and a member of the ABCC family such as ABCC3) and possibly other transporters or resistance mechanisms, could explain why inhibition of a single transporter may not be an effective therapeutic strategy (Marzac et al, 2011; van den Heuvel-Eibrink et al, 2005). Along this same line, a recent report suggested that ABCG2 can be overexpressed in leukemias with a FLT3 internal tandem duplication, with an association between ABCG2 overexpression and reduced disease-free and overall survival but not with response rate (Tiribelli et al, 2011). This finding suggests an association of ABCG2 with the intrinsic biology of the leukemia rather than with drug efflux mediating resistance per se.…”
Section: The Expression and Role Of Abc Transporters In Amlmentioning
confidence: 95%
“…Co-ordinate regulation of ABCG2 with ABCB1 (and a member of the ABCC family such as ABCC3) and possibly other transporters or resistance mechanisms, could explain why inhibition of a single transporter may not be an effective therapeutic strategy (Marzac et al, 2011; van den Heuvel-Eibrink et al, 2005). Along this same line, a recent report suggested that ABCG2 can be overexpressed in leukemias with a FLT3 internal tandem duplication, with an association between ABCG2 overexpression and reduced disease-free and overall survival but not with response rate (Tiribelli et al, 2011). This finding suggests an association of ABCG2 with the intrinsic biology of the leukemia rather than with drug efflux mediating resistance per se.…”
Section: The Expression and Role Of Abc Transporters In Amlmentioning
confidence: 95%
“…Tiribelli et al [161] found a significant positive correlation between BCRP overexpression and fms-like tyrosine kinase 3 internal tandem duplication (FLT3-ITD) (p=0.002), and while CR attainment correlated with neither, DFS was shorter in patients with blast BCRP expression (p=0.046), and shortest in those with both BCRP expression and FLT3-ITD (p=0.023). FLT3 signaling inhibitors are in clinical trials in AML for patients with a FLT3-ITD.…”
Section: Section 4 Recent Findings In Acute Leukemia and Other Hematmentioning
confidence: 99%
“…MDR1 expression was associated with lower CR rates but not decreased OS rates in a study of 405 patients with AML (Illmer et al, 2002); the homozygous wild-type genotype was associated with a decreased OS rate and an increased risk of relapse, which suggests that mechanisms in addition to P-gp expression are involved. An analysis of MDR1 expression and FLT3-ITD mutation status among 166 adult patients with AML demonstrated shorter times to relapse for MDR1-overexpressing patients and poor disease-free survival rates for patients with both MDR1 overexpression and FLT3-ITD ϩ status (Tiribelli et al, 2011). The parameter of P-gp expression also has been shown to be associated with responses and outcomes.…”
Section: Mdr In Acute Myeloid Leukemia and Other Acutementioning
confidence: 99%